The Geographical Distribution of Cutaneous Leishmaniasis Causative Agents in Iran and Its Neighboring Countries, A Review - Ghatee, Mohammad Amin; Taylor, Walter R.; Karamian, Mehdi (Frontiers in Public Health, 2020)
Leishmania tropica and Leishmania major are both the main cause of anthroponotic (ACL) and zoonotic cutaneous leishmaniasis (ZCL), respectively, in the Old World. Leishmania infantum and Leishmania donovani, which are important causes of visceral leishmaniasis, have also occasionally been reported in CL patients. The present study investigates the current distribution of causative species of CL in Iran and neighboring countries in the Middle East. There has been expansion of L. tropica into new urban and rural foci in Iran, with well-documented cases of visceralization, a substantial increase of CL in Syria, and the emergence of new foci and outbreaks in Turkey and Iraq, especially due to L. major. Civil war in Syria and Iraq, population movement, poverty, and climatic change play important roles in the changing CL distribution in this region. Control programs should adopt a multidisciplinary approach based on active surveillance and case finding, especially in vulnerable refugee populations, determination of hazard maps for CL hot points using GIS and other advanced technology, the free distribution of drugs, rodent control, and greater community engagement in poor and marginalized populations. Comprehensive molecular studies that could show the species and strains of Leishmania in different areas of each country can give a better view from the distribution of CL in this region.